Impact of Talent Management Practices on Employee Performance: An Empirical Study Among Healthcare Employees - Munaza Bibi (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose- The purpose of this study was to determine the effect of talent management practices on employee performance among employees working in healthcare organizations of Pakistan. Design/Methodology- This study employed a cross-sectional design and quantitative approach. To select the sample from the population convenience sampling was utilized. The sample of the study was comprised of 364 employees working in healthcare organizations to determine the performance of employee because of talent management practices. Questionnaire was used for collection of data. Findings- The outcomes of the study revealed a significantly positive effect of talent management practices i.e. recruitment and selection for talent attraction, coaching and mentoring for learning and development of talent, compensation for retention of talent on employee performance. Practical Implications- The results of study might help human resource management department of health care organizations through executing practices to manage talented employees can help them to motivate employee to perform effectually to meet the organizational objectives. Health care organizations should develop strategies and practices to manage the talent to be able to embrace changes through attracting, developing and retaining the talented employees to tackle the current and future needs of organization.